2018
DOI: 10.1002/pc.24978
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, dynamic, and thermomechanical properties of coir/pineapple leaf fiber reinforced polylactic acid hybrid biocomposites

Abstract: Natural fiber‐based polymer composites have been widely studied to substitute synthetic materials. In this research, pineapple leaf fibers (PALF) and coir fibers (CF) were loaded into a polylactic acid (PLA) matrix to develop composite materials with improved mechanical and thermal properties, which could be potentially applied as biodegradable food packaging. Biocomposites with different fiber ratios were manufactured using an internal mixer plasticizer and a hot press machine. Mechanical and thermal analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 74 publications
1
71
0
1
Order By: Relevance
“…PLA has been previously reported by Birnin-Yauri et al [30] to have high strength, modulus, and biocompatibility. The fiber–matrix ratio in the biocomposite is 30:70 according to previous studies done on PALF biocomposites [31].…”
Section: Resultsmentioning
confidence: 99%
“…PLA has been previously reported by Birnin-Yauri et al [30] to have high strength, modulus, and biocompatibility. The fiber–matrix ratio in the biocomposite is 30:70 according to previous studies done on PALF biocomposites [31].…”
Section: Resultsmentioning
confidence: 99%
“…Several natural reinforcements can be found in literature, including flax, hemp, jute, sisal, cotton, silk, and others . Among these classes of materials, hemp‐reinforced polymeric composites are especially suitable to be applied in industrial design because of their unique mechanical and physical properties …”
Section: Introductionmentioning
confidence: 99%
“…They incorporated a 1:1, 3:7, or 7:3 ratio of coconut to pineapple at 30 wt% or 30 wt% of either into a PLA matrix. The authors found that the hybrid combinations of the fibers performed better than the individual fiber types alone (Siakeng et al 2019). The authors attributed this result to the combination of fibers overcoming the inherent disadvantages of each of the fiber types individually.…”
Section: Pineapplementioning
confidence: 99%